Cold-tolerant strains of Puccinia striiformis f.sp. tritici (MLG1 and MLG2) persist under snow, triggering early epidemic of stripe rust in the Xinjiang region, China - Awais, Muhammad; Jiao, Haocheng; Peng, Xueqing; Li, Li; Ali, Sajid; Zhao, Jie; Kang, Zhensheng; Ma, Jinbiao (Frontiers in Plant Science, 2026)
Global warming has changed snowfall patterns in recent years worldwide, which affected the timing and severity of wheat stripe rust outbreaks. In wheat-growing areas of Xinjiang, China, where cold temperatures prevail and snow typically accumulates after cultivation, stripe rust epidemics have traditionally emerged after snowmelt. However, the recently delayed snowfall in some regions has led to earlier-than-expected outbreaks. The role of spores of different Puccinia striiformis f.sp. tritici (Pst) genotypes surviving under snow remains largely unexplored. We performed Pst sampling at three stages in the Yili region of Xinjiang: (i) previous crop in summer May 2023, (ii) early infection before snowfall in the next winter cropping season during December 2023, and (iii) post-snowmelt sampling from the same crop in March 2024. We used 17 SSR markers to genotype 486 Pst isolates. Our findings revealed that snow survival enables cold-tolerant strains of Pst, contributing to the early stripe rust epidemics in the Yili region of Xinjiang in December 2023. Structure analysis revealed a similar genetic group across different seasons and before and after snowmelt populations. MLG analysis identified that MLG-1 and MLG-2 persisted from the summer 2023 crop, early winter seedlings before snow, and after snowmelt in the 2024 crop. While some multilocus genotypes, such as MLG_60, MLG_62, MLG_67, and MLG_83, are not viable under snow cover, the genetic diversity of Pst declined between summer and early winter crops (Simpson diversity = 0.8 to 0.7). The genetic diversity of Pst increased between before and after the snowmelt crop (Simpson diversity = 0.7 to 0.9). It suggested that a possible invasion of migratory genotypes or continued sporulation happened after infection beneath the snow. The cold-tolerant strains of Pst (MLG1 and MLG2) are responsible for the early epidemic in the Yili region of Xinjiang during seedling stage, where temperatures are below freezing and they can survive under snow covers in winter. Pst can also overlap with summer and winter crops to survive year-round in this region. Monitoring the migration pattern of these strains is crucial as it causes disease in wheat seedlings, leading to more crop losses compared to other lineages that infect mature crops.